Lyricism as an element of cordocentrism in the memoirs of Anna Barvinok (Literatures of the World: Poetics, Mentality and Spirituality, 2017)
In this article Hanna Barvinok`s memoirs are analysed. The main attention is paid to lyricism of memorials about T.Shevchenko and P.Kulish which are written according to heart philosophy which is a feature of mentality of Ukrainian people.
Keywords: memoirs; heart philosophy; genre; poetry in prose; memorials